Investigation of the molecular mechanism of Xiaoluo Wan in thyroid-associated ophthalmopathy: network analysis and in vivo study - Wenchao Gu; Shuo Tian; Lu Fu; Lina Wang; Liangkun Zhang; Furong Wang (Hereditas)
Abstract Background Thyroid-associated ophthalmopathy (TAO) is a common complication of hyperthyroidism that can significantly impair quality of life. This study investigated the effects and mechanisms of Xiaoluo Wan (XLW), a traditional Chinese herbal prescription, in treating TAO. Methods The protective effects of XLW on the extraocular muscles were first examined in hyperthyroid rats. Network analysis strategies were applied to predict potential targets and therapeutic mechanisms associated with XLW. The expression of key genes and proteins was subsequently validated and analyzed in rats with hyperthyroidism. Results XLW alleviated the pathological changes in the extraocular muscles caused by hyperthyroidism. The network analysis identified 66 effective targets. The core targets of XLW against TAO included AKT1, PTGS2, BCL2, IL10, IL1b, CCL2, IFNG, IL6, MMP9, TGFB1, HIF1α, and TP53. Enrichment analysis suggested that the amelioration mechanisms of XLW may be linked to the HIF1 signaling pathway. In hyperthyroid rats, XLW reduced oxidative stress (OS) in extraocular muscle and inhibited the expression of HIF-1ɑ. Additionally, XLW exerted regulatory actions on the expression of various proteins closely linked to HIF-1α and OS. Conclusions XLW reduces injuries to extraocular muscles in hyperthyroidism, possibly by inhibiting OS via HIF1 signaling. This may provide novel insights into the pharmacological mechanism of XLW in treating TAO.